Electromyographic patterns of the rat hindlimb in response to muscle stretch after spinal cord injury. Issue 6 (June 2018) - Keller, Anastasia; Rees, Kathlene; Seibt, Erik; Wood, B.; Wade, Abigail; Morehouse, Johnny; Shum-Siu, Alice; Magnuson, David
Abstract Study design Experimental Study. Objectives To characterize the specific hindlimb electromyographic (EMG) patterns in response to muscle stretch and to measure the applied forces during stretching in the rat model of moderate SCI. Setting Kentucky Spinal Cord Injury Research Center, Louisville, KY, USA. Methods Female Sprague Dawley rats (n = 4) were instrumented for telemetry-based EMG recording (right rectus femoris and biceps femoris) and received a moderate T10 spinal cord injury (SCI). The major hindlimb muscle groups were stretched using our clinically modeled protocol. The EMG responses were recorded biweekly for 8 weeks. The forces applied during stretching were measured using a custom-designed glove. Locomotor function was assessed using the BBB Open Field Locomotor Scale, 3D kinematics and gait analysis. Results Three main EMG patterns in response to stretch were identified: clonic-like, air-stepping, and spasms. Torques applied during stretching ranged from 0.4-8 Ncm, and with the exception of the quadriceps, did not change significantly over the weeks of stretching. Two stretching sessions a week did not result in a significant disruption to locomotor function. Conclusions Stretching evokes EMG patterns in rats similar to those reported in humans including clonus and spasms. The torques used during stretching are comparable, based on the ratio of torque to body weight, to the few previously published studies that measured the forces and/or torques applied by physical therapists when stretching patients. Future studies are warranted to fully explore the impact of muscle stretch on spinal cord function after injury. Sponsorship DoD, KSCHIRT, NIH.